Ethics Committees at Work - Schwartz, Robert L. (Cambridge quarterly of healthcare ethics, 1994)
Lillian T. is a 22-year-old woman with Down Syndrome. Cared for by her mother, she has lived all her life in the same small town and is a quiet, cooperative, and happy individual. Her main pleasures revolve around a steady routine that includes sewing in a sheltered workshop 5 days each week. She performs her own washing and dressing, makes simple meals for herself, and enjoys television.